2003
DOI: 10.1021/ja029100q
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fluorophores for Single-Molecule Imaging

Abstract: A new class of fluorophores has been identified that can be imaged at the single-molecule level and offer additional beneficial properties such as a significant ground state dipole moment, moderate hyperpolarizability, and sensitivity to local rigidity. These molecules contain an amine donor and a dicyanodihydrofuran (DCDHF) acceptor linked by a conjugated unit (benzene, thiophene, alkene, styrene, etc.) and were originally designed to deliver both high polarizability anisotropy and dipole moment as nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 38 publications
3
69
0
Order By: Relevance
“…However, the disadvantages of the azido DCDHF system are: it is not genetically targeted, as fluorescent proteins are; DCDHFs with a primary amine exhibit more blinking than those with secondary or tertiary amines (see Figure 7 and reference [13]); and the photoactivation is irreversible (once the fluorophore photobleaches, it cannot be reactivated, which is possible in some photoswitches[55-60]).…”
Section: Structure-property Designmentioning
confidence: 99%
“…However, the disadvantages of the azido DCDHF system are: it is not genetically targeted, as fluorescent proteins are; DCDHFs with a primary amine exhibit more blinking than those with secondary or tertiary amines (see Figure 7 and reference [13]); and the photoactivation is irreversible (once the fluorophore photobleaches, it cannot be reactivated, which is possible in some photoswitches[55-60]).…”
Section: Structure-property Designmentioning
confidence: 99%
“…[1,2] Our purpose in this work was to design and characterize dyes that 1) respond to medium polarity by solvatochromic shifts of their fluorescence emission band, and 2) meet all the stringent requirements for single-molecule spectroscopy. [3,4] We have found that the amino-substituted perylene imides 5PI and 6PI (Scheme 1) indeed combine excellent detectability at the single-molecule level with substantial solvatochromic sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The DCDHF fluorophores are comparatively photostable, sensitive to local environment, and their chemistries and photophysics are tunable to optimize absorption wavelength, membrane affinity, and solubility. [4][5][6][7][8][9][10][11][12][13][14] We have now reengineered the DCDHFs to make them photoactivatable: by replacing the amine with an azide, the fluorescence is quenched; upon photocleaving the azide, the amino fluorophore is regenerated, and the fluorescence returns. 13 In this paper, we review the properties of the DCDHF class in general, and then present the scheme that has been utilized to make them photoswitchable.…”
Section: Introductionmentioning
confidence: 98%